Answer: 10
Step-by-step explanation:
tony is 5 years younger than Marvin's age 1 year from now.
t = (m+1) - 5
t = m - 4
6 years ago tony was half as old as marvin was then.
t - 6 = 1/2(m - 6)
Get rid of the fraction, multiply both sides by 2
2(t-6) = m - 6
2t - 12 = m - 6
2t = m - 6 + 12
2t = m + 6
from the first statement, replace t with (m-4)
2(m-4) = m + 6
2m - 8 = m + 6
2m - m = 6 + 8
m = 14 is Marvin's present age
:
how old is tony now?
t = 14 - 4
t = 10 yrs is tony's age
Answer:
(1) 1 and 7
Step-by-step explanation:
Hello!
We can solve by isolating the variable.
<h3>Solve</h3>
- 3(x - 4)² = 27
- (x - 4)² = 9
- √(x - 4)² = √9
- (x - 4) = ± 3
- x = 4 ± 3
There are two solutions, 1 and 7.
The answer is option 1: x = 7, x = 1.
v-10=-9
Solve for v.
Add 10 to each side of the equation:
v-10+10 =-9+10
v= 1